The rough guide to Australia 2025 - Chipperfield, Mark; Zatko, Martin (Rough Guides, 2025)
Ideal for independent travellers, this guidebook to Australia, written by experts, goes beyond the basics. It blends must-see sights with hidden gems and offers unmatched practical guidance for seamless planning and on-the-go exploration. Packed with in-depth advice often missing from other guides, it helps you navigate with ease.